The blood in systemic disease. (May 2017) - Bain, Barbara
Abstract: Systemic disease has protean manifestations. Most frequently observed is anaemia of chronic disease, anaemia can also be autoimmune, microangiopathic, mechanical or caused by haematinic deficiency, bone marrow replacement or pure red cell aplasia. The platelet count can be increased or decreased. The number of neutrophils, eosinophils, monocytes and lymphocytes can be increased, but neutropenia, eosinopenia and lymphopenia can also occur. Leucocytes can appear activated. Systemic disease can lead to thromboembolism, haemorrhage or disseminated intravascular coagulation. Lymphoma can occur as a result of viral infection, immune deficiency or the treatment of systemic disease.